Optimization of heat recovery system parameters with a glass furnace recuperator - Fialko, N.; Stepanova, A.; Navrodska, R.; Shevchuk, S.; Sbrodova, H. (Energy and Automation, 2025)
The modern development of the energy sector is characterized by a significant increase in the cost of energy and natural resources, as well as growing requirements for environmental protection from the impact of waste produced by municipal and industrial enterprises. Currently, the problem of energy saving in the municipal heat-power engineering is to some extent solved by recovering the heat of fuel combustion materials. Increasing the efficiency of the relevant heat recovery equipment is important and urgent. The purpose of the study is to optimize the parameters of a heat recovery system with a regenerative-type industrial furnace recuperator based on a complex multi-level optimization, statistical theory of experiment planning, and functional analysis. To achieve this purpose, the following tasks were set: to develop a multi-level optimization scheme and a recursive bypass scheme of optimization levels for a heat recovery system with a glass melting furnace recuperator; to develop mathematical models for each optimization level and obtain functional dependencies of the system efficiency assessment criteria on the main parameters based on statistical methods of experiment planning and functional analysis methods; to determine the optimal values of the operating and constructive parameters of the heat recovery system. The basic principle of the multi-level optimization method is as follows. When constructing a mathematical model of each optimization level, the variable parameters are the parameters that vary for the objects of this level, and the constant parameters are the optimal parameters that are the results of solving local optimization problems of other levels. The main task when using the statistical methods of the experiment planning theory and functional analysis methods is to determine the functional dependencies of the criteria for assessing of the studied heat recovery system efficiency on its main parameters. The research results of the operating and constructive parameters of a heat recovery system that includes a waste heat recuperator of a regenerative type gas-consuming industrial furnace are presented. The recuperator is designed to heat the combustion air by heat recovering of the exhaust gases after the furnace regenerators. The recuperators are assembled of the required number of modules depending on the exhaust gas consumption. The heat exchange surface of the module is made up of steel panels formed by pipes with membranes. Exhaust gases move in the inter-panel space, and air moves in the pipe space. To intensify heat transfer from the air side, the pipes have with flow turbulators. A multi-level optimization scheme and a recursive bypass scheme of optimization levels for the studied heat recovery system were developed. The optimal values of the operating and constructive parameters of the heat recovery system using the specified complex methodology were calculated. The methodology allows you to determine the parameters that are as close to optimal as possible. This increases the heat recovery efficiency of exhaust gases by an average of 2.5% to 3% compared to the efficiency of systems optimized using other optimization methods. Key words: heat recovery; heat recovery of exhaust gases; complex research methods